Weld cracking in ferrous alloys - Singh, Raman (Woodhead Publishing in materials., 2009)
Weld cracks are unacceptable defects that can compromise the integrity of welded structures. Weld cracking can lead to structural failures which at best will require remedial action and at worst can lead to loss of life. Weld cracking in ferrous alloys reviews the latest developments in the design, evaluation, prevention and repair of weld cracks. Part one reviews the fundamentals as well as recent advances in the areas of welding technology, design and material selection for preventing weld cracking. Part two analyses weld crack behaviour, evaluation and repair of cracking/cracked welds. The book benefits from an extensive and robust chapter on the topic of NDE and quality control that was contributed by one of the most respected non-destructive evaluation and development groups in the world. Part three covers environment assisted weld cracking. With its distinguished editor and international team of contributors, Weld cracking in ferrous alloys is a valuable source of reference for all those concerned with improving the quality of welding and welded components. In the planning and development of this book, particular care has been taken to make the chapters suitable for people from other disciplines who need to understand weld cracking and failure. Reviews the latest developments in the design, evaluation, prevention and repair of weld cracksAssesses recent advances in welding technology, design and material selectionAnalyses weld crack behaviour, evaluation and repair including environment assisted weld cracking.